A Compact Metamaterial Dual-band Branch-line Coupler for 5G Applications (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This study introduces a compact branch-line coupler (BLC) based on metamaterial (MTM) technology that can operate in sub-6 GHz 5G frequency bands. Conventional vertical and horizontal sections of the BLC were replaced with T-shaped TLs and interdigital capacitor (IDC) unit cells incorporated into the BLC sections to improve their performance and reduce their dimensions. The BLC is designed on a Rogers RT5880 substrate material, and it operates at dual frequencies of 0.7 GHz and 3.5 GHz. The design was simulated using CST Microwave Studio software and achieved enhanced frequency band ratio.